Risk of mortality and level of serum alanine aminotransferase among community-dwelling elderly in Israel. Issue 12 (December 2018) - Schmilovitz-Weiss, Hemda; Gingold-Belfer, Rachel; Boltin, Doron; Beloosesky, Yichayaou; Meyerovitch, Joseph; Tor, Ruth; Issa, Nidal; Grossman, Alon; Koren-Morag, Nira; Weiss, Avraham
Abstract : Background: Serum alanine aminotransferase (ALT) levels below and above the reference range have been found to serve as a marker of liver injury and to predict all-cause mortality. The need to adjust the reference range by age, sex, or other parameters remains unclear. The current reference range of serum ALT in Israel is 0–34 IU/l for women and 0–45 IU/l for men. We aimed to test the applicability of the current reference range values of ALT in specific people – the elderly population. Methods: A retrospective design was used. The study population consisted of community-dwelling individuals aged at least 65 years who were tested for serum ALT in 2002 at a large health management organization and followed until the end of December 2012. Data were collected on demographics, laboratory tests, comorbidities, and mortality. Results: A total of 49 634 participants (59% women, mean age 83.2±6.3 years) were included. ALT levels between 16 and 25 IU/l were associated with the lowest mortality (hazard ratio=1), and values of less than 16 IU/l and more than 25 IU/l (unadjusted) were associated with higher mortality risk, yielding a U-shaped pattern. Highest mortality rates were also revealed at serum ALT levels more than 56 IU/l and less than 10 IU/l. A significant association of higher mortality risk was noted with lower mean values of hemoglobin, albumin, and total cholesterol, both for patients with lower serum ALT levels (<10 IU/l) and patients with higher serum levels (>56 IU/l). Conclusion: Very low and very high levels of serum ALT within the current reference range are associated with an increased risk of death in community-dwelling individuals of at least 65 years old.